Application of magnetic field hyperthermia and superparamagnetic iron oxide nanoparticles to HIV-1-specific T-cell cytotoxicity. - Williams, J; Southern, P; Lissina, A; Christian, H; Sewell, A; Phillips, R; Pankhurst, Q; Frater, J (2013)
The latent HIV-1 reservoir remains the major barrier to HIV-1 eradication. Although successful at limiting HIV replication, highly active antiretroviral therapy is unable to cure HIV infection, thus novel therapeutic strategies are needed to eliminate the virus. Magnetic field hyperthermia (MFH) generates thermoablative cytotoxic temperatures in target-cell populations, and has delivered promising outcomes in animal models, as well as in several cancer clinical trials. MFH has been proposed as a strategy to improve the killing of HIV-infected cells and for targeting the HIV latent reservoirs. We wished to determine whether MFH could be used to enhance cytotoxic T-lymphocyte (CTL) targeting of HIV-infected cells in a proof-of-concept study. Here, for the first time, we apply MFH to an infectious disease (HIV-1) using the superparamagnetic iron oxide nanoparticle FeraSpin R. We attempt to improve the cytotoxic potential of T-cell receptor-transfected HIV-specific CTLs using thermotherapy, and assess superparamagnetic iron oxide nanoparticle toxicity, uptake, and effect on cell function using more sensitive methods than previously described. FeraSpin R exhibited only limited toxicity, demonstrated efficient uptake and cell-surface attachment, and only modestly impacted T-cell function. In contrast to the cancer models, insufficient MFH was generated to enhance CTL killing of HIV-infected cells. MFH remains an exciting new technology in the field of cancer therapeutics, which, as technology improves, may have significant potential to enhance CTL function and act as an adjunctive therapy in the eradication of latently infected HIV-positive cells.